Study on the additional financial burden of breast cancer disease on cancer patients and their families. Financial toxicity in cancer - Fernandez-Rodriguez, Eduardo J.; Taboada-Taboada, Rocio; Garcia-Martin, Alberto; Sanchez-Gomez, Celia; Saez-Gutierrez, Susana; Rihuete-Galve, Maria I.; Fonseca-Sánchez, Emilio (Frontiers in Public Health, 2024)
Introduction Breast cancer is among the most frequently diagnosed cancers worldwide, with 2.3 million new cases reported annually. The condition causes a social and economic impact known as financial toxicity of cancer. The study aims to explore the extra expenses borne by patients and their families on being diagnosed with breast cancer. Methodology An observational, descriptive, cross-sectional study was conducted. The data was collected between November 2021 and March 2022 at the Medical Oncology Service in Complejo Asistencial Universitario de Salamanca, Spain. The variables under investigation were additional economic costs, physical disability (as measured by the Barthel Index), instrumental activities of daily living (as measured by the Lawton-Brody Scale), and caregiver burden (measured using the ZARIT scale). Results The final sample size was N = 107. The study yielded the following outcomes: the median age was 55 years old and the majority of participants were female, with a proportion of 99.1%. The incidence rates for stage I and II were 31.8 and 35.5%, respectively. The median Barthel score was 100 points, while the Lawton and Brody score were 8 points and the ECOG score was 2 points. The analysis of primary caregiver burden resulted in a median ZARIT score of 15 points. The expenses related solely to the cancer diagnosis totaled 1511.22 euros per year (316.82 euros for pharmaceuticals; 487.85 euros for orthopedic equipment; 140.19 euros for home help; and 566.36 euros for housing adaptation or transfer to a hospital). The average annual income before diagnosis was 19962.62 euros. However, after being diagnosed with breast cancer, there is a significant income decrease of 15.91%, resulting in a reduced average annual income of 16785.98 euros. Additionally, a significant correlation was found between total expenditure and the level of dependency (p = 0.032) and functional status (p = 0.045). Conclusion These findings indicate that breast cancer patients experience a considerable economic burden, which worsens as their functional status deteriorates. Therefore, we believe policies should be implemented to help control this economic deterioration resulting from a serious health condition.